Jurisprudential Inquiry Based on Edmodo to Improving Students Critical Thinking in Citizenship Education Courses - Syafawati, Zulfah Lis; Murdiono, Mukhamad; Suyato, Suyato (Universitas Pendidikan Ganesha, 2022)
This study aims to prove and analyze the application of the jurisprudential inquiry method based on the Edmodo electronic learning media to improve students' critical thinking skills in the Citizenship Education course. This type of research uses classroom action research by developing a model from Stephen Kemmis & Robin McTaggart in the form of a cycle of planning, action and observation, and reflection. The research subjects were 32 students. The data collection technique used a structured observation instrument and a free description test. The data analysis technique used descriptive statistics frequencies with the help of the SPSS 24 application to process the data from the student critical thinking observation questionnaire, the one sample t test with SPSS 24 to see the results of student learning completeness, and the nonparametric test - binomal test with SPSS 24 to see the results classical student learning mastery. The results showed that the high level of critical thinking of students in the Citizenship Education course by applying the jurisprudential inquiry learning method assisted by the Edmodo application. Learning Citizenship Education is no longer a boring subject for students because lecturers can apply learning methods and learning media that are combined innovatively, creatively, and effectively.